IDDF2022-ABS-0170 Hypoxia and R-factor: predictors of abnormal lft in covid-19. (2nd September 2022) - Chew, Weida; Kuang, Jonathan; Lin, Huiyu; Ang, Li Wei; Yang, Wei-Lyn; Lye, David; Young, Barnaby Edward
Abstract : Background: Liver function test (LFT) abnormalities in COVID-19 patients are commonly mild. However, a proportion develops significant liver injury, with conflicting data about the association of LFT abnormalities with COVID severity. This retrospective observational study from Singapore assessed the impact of abnormal alanine aminotransferase (ALT) on the clinical course of COVID-19 and elucidated risk factors associated with the development of abnormal ALT in an unvaccinated population. Methods: We looked at 669 unvaccinated hospitalised COVID-19 patients at the National Centre for Infectious Diseases (NCID), Singapore, from 23rd January-15th April 2020. Excluding patients with abnormal baseline ALT or only 1 ALT reading, 163 patients were analysed for their baseline demographics and clinical characteristics (IDDF2022-ABS-0170 Table 1). Multivariate analysis was performed to evaluate factors predictive of developing abnormal ALT.R-factor, used in clinical practice to objectively define different patterns of liver injury, was calculated as (ALT/upper limit of normal (ULN) of ALT)/(alkaline phosphatase(ALP)/ULN of ALP). Results: 30.7% of patients developed abnormal ALT: they were more likely to be older and had comorbidities of hyperlipidaemia and hypertension. Multivariate logistic regression (IDDF2022-ABS-0170 Table 2) showed that R-factor ≥1 on admission (aOR 3.13, 95%CI 1.41–6.95) and hypoxia (aOR3.54, 95%CI 1.29–9.69) were independent risk factors for developing abnormal ALT, but not medications or comorbidities. The R-factor on admission trended higher for patients who developed abnormal LFT as compared to those who didn't, regardless of the day of illness (IDDF2022-ABS-0170 Figure 1. R-factor). The patients who developed abnormal ALT also ran a more severe course of illness with a greater proportion needing supplementary oxygen (58%vs18.6%, p <0.0005), admission to Intensive Care/High Dependency Unit (32%vs11.5%, p=0.003) and intubation (20%vs2.7%, p<0.0005). The death rate between the 2 groups was similar. Conclusions: Liver injury is associated with poorer clinical outcomes in COVID-19 patients. R-factor ≥1 on admission and hypoxia are independent risk factors for developing abnormal ALT in COVID-19. More studies are required to see if the incorporation of the R-factor into conventional clinical risk scores can improve the performance in predicting disease progression/discriminating disease severity and applicability in emerging virus variants.